Isolated‐Oxygen‐Vacancy Hardening in Lead‐Free Piezoelectrics. Issue 29 (13th June 2022) - Liu, Yi‐Xuan; Qu, Wanbo; Thong, Hao‐Cheng; Zhang, Yang; Zhang, Yunfan; Yao, Fang‐Zhou; Nguyen, Trong Nghia; Li, Jia‐Wang; Zhang, Mao‐Hua; Li, Jing‐Feng; Han, Bing; Gong, Wen; et al.
Abstract: Defect engineering is a well‐established approach to customize the functionalities of perovskite oxides. In demanding high‐power applications of piezoelectric materials, acceptor doping serves as the state‐of‐the‐art hardening approach, but inevitably deteriorates the electromechanical properties. Here, a new hardening effect associated with isolated oxygen vacancies for achieving well‐balanced performances is proposed. Guided by theoretical design, a well‐balanced performance of mechanical quality factor ( Q m ) and piezoelectric coefficient ( d 33 ) is achieved in lead‐free potassium sodium niobate ceramics, where Q m increases by over 60% while d 33 remains almost unchanged. By atomic‐scale Z ‐contrast imaging, hysteresis measurement, and quantitative piezoresponse force microscopy analysis, it is revealed that the improved Q m results from the inhibition of both extrinsic and intrinsic losses while the unchanged d 33 is associated with the polarization contributions being retained. More encouragingly, the hardening effect shows exceptional stability with increasing vibration velocity, offering potential in material design for practical high‐power applications such as pharmaceutical extraction and ultrasonic osteotomes. Abstract : A novel strategy is developed for the hardening of piezoelectrics via the mediation of dopant‐exclusive oxygen vacancies to overcome the long‐term issue: the dilemma between the mechanical quality factor and piezoelectricity coefficient. The approach also makes the high‐power performance superior to many state‐of‐the‐art counterparts, offering a possible route to various piezoelectrics for high‐end applications.